2015
DOI: 10.1164/rccm.201409-1704oc
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of QuantiFERON-TB Gold In-Tube Conversion and Reversion in a Cohort of South African Adolescents

Abstract: Rationale: Interferon-g release assays are used to diagnose tuberculosis infection. In developed countries, high rates of reversion following conversion have been described.Objectives: To assess QuantiFERON TB Gold In-Tube test (QFT) conversion and reversion dynamics in a tuberculosisendemic setting.Methods: Adolescents aged 12-18 years residing near Cape Town were recruited. Tuberculin skin tests (TSTs) and QFTs were performed at baseline and after 2 years of follow up. Half of the participants had TST and QF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
4
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 33 publications
4
109
4
1
Order By: Relevance
“…Shah and colleagues 42 found low rates of reversion (15%) among QFT-positive household contacts of tuberculosis cases. In this study, we found high overall rates of QFT reversion among young children (58%) and, as seen in our adolescent study, 20 we found an inverse relation between QFT conversion interferon-γ value and reversion risk; however, reversion rates remained fairly high (20%) even at very high interferon-γ values (>4·00 IU/mL).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Shah and colleagues 42 found low rates of reversion (15%) among QFT-positive household contacts of tuberculosis cases. In this study, we found high overall rates of QFT reversion among young children (58%) and, as seen in our adolescent study, 20 we found an inverse relation between QFT conversion interferon-γ value and reversion risk; however, reversion rates remained fairly high (20%) even at very high interferon-γ values (>4·00 IU/mL).…”
Section: Discussionsupporting
confidence: 81%
“…We note that this bimodal distribution differs from the unimodal distribution of QFT values reported in adolescent and adult studies, including one from the same laboratory and community, suggesting that the naive infant immune response to M tuberculosis might differ from that of adults. 20 For our main analyses, we selected a threshold of 4·00 IU/mL based on disease and reversion risks above this inflection point ( figure 3) and availability of interferon-γ standards up to 4·00 IU/mL in the international kits. We note that high rates of disease (2·5 per 100 person-years) were found even among those with QFT values 0·35-4·00 IU/mL, and the optimal threshold from a perspective of targeting interventions might be lower.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cohort study conducted in adolescents in the Western Cape region of South Africa with high rates of TB showed approximately 50% of high school students were IGRA positive [12,13]. Annual IGRA conversion rates (from negative to positive) in the same population were 14% [14]. Using a conservative estimate in this population of 10% annual IGRA conversion and a 0.05% statistical error, a trial of a vaccine that was 60% effective would require on the order of 1000 participants (500 in each study arm) to be followed for one year after vaccination to detect an impact on infection as determined by IGRA conversion.…”
Section: Prevention Of Infectionmentioning
confidence: 99%